Clinical study of melatonin effects about sleep quality and pulmonary function in chronic obstructive pulmonary disease - Deuzilane Muniz Nunes (2007)
Disturbed sleep is in common Chronic Obstructive Pulmonary Disease (COPD). Conventional hypnotics worsen nocturnal hypoxemia and can lead to respiratory failure in severe cases of this condition. Melatonin administration has been reported to ameliorate sleep problems in several clinical conditions and is generally considered to be safe. The aim of this study was to evaluate the effect of 21 days of melatonin administration on subjective sleep quality in ambulatory patients with clinically stable COPD. This was a randomized, double-blind, placebo-controlled study on the effects of melatonin on sleep in COPD. Twenty-five patients with moderate to very severe COPD were randomized to receive either melatonin 3 mg (n=12) or placebo (n=13) for 21 days. Sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI); daytime sleepiness was measured by the Epworth Sleepiness Scale (ESS); life quality was assessed by St. Georgeâs Respiratory Questionnaire (SGRQ); pulmonary function and functional exercise level were assessed, respectively, by spirometry and the six-minute walk test. These tests were repeated at the end of the treatment for comparison. Sixteen patients (64%) presented poor-quality sleep on initial evaluation. Melatonin treatment significantly improved sleep (p= 0.012). No changes in daytime sleepiness, quality of life, lung function and functional exercise level were observed. We conclude that melatonin can improve subjective sleep quality in COPD. Further studies into the safety of long-term melatonin use are needed before it can be recommended for the management of sleep disturbances in these patients